Impak kilang simen terhadap penghasilan PM10 di Rawang, Selangor Darul Ehsan - Mohamad Ihsan Muhamad Ismail (Tanjong Malim, 2016)
Impak kilang simen terhadap penghasilan PM10 di Rawang, Selangor Darul Ehsan by Mohamad Ihsan Muhamad Ismail